e- Health - Guidelines for State Policy Formation in the Healthcare Sector of Bulgaria - Vyara Tserovska; Stoyan Denchev (Budapest International Research and Critics University, 2021)
The active reform of the Bulgarian society requires new approaches and full use of information processes for management in the healthcare system. Despite the transformations that have taken place in this area, many issues are yet to be resolved. E-Health is a collection of applications based on advanced information and communication technologies within an organisational and legal framework covering the whole aspect of healthcare, from diagnosis to the time of completion and payment for the treatment. The inconsistencies identified between the high requirements of modern health care, the need to implement the eHealth and the significant falling behind of the project implementation process can only be addressed by implementing a national strategy regulating the objectives, scope and stages of the creation of a single intergrated health information system.